Simultaneous Determination of Phenolic Compounds in Leptadenia pyrotechnica (Forssk.) Decne. by Using High-Performance Liquid Chromatography (HPLC-DAD-UV) - Raman Preet; Raghbir Chand Gupta (Hindawi Limited, 2018)
During the present study, an endeavor has been made to produce a simple, rapid, and simultaneous method for determination of phenolic compounds by using high-performance liquid chromatography in aerial parts of Leptadenia pyrotechnica (Forssk.) Decne. collected from the Indian Thar Desert. The optimized process was used for the quantification of ten phenolic compounds. The chromatographic separation was accomplished on an Atlantis T3 column at 25°C with isocratic elution. A mixture of acetonitrile and water was used as the mobile phase at a flow rate of 0.8 mL/min. The linear regression examination data for the calibration plots displayed a good linear relationship with r2 > 0.999 in the concentration range of 2-20 µL. In the methanolic extracts of the whole plant of L. pyrotechnica, the content of caffeic acid (3.3%) was reported to be the highest concentration.